PEMBUATAN PENGAWET ALAMI DARI EKSTRAK KAYU NANGKA DENGAN MALTODEKSTRIN UNTUK MENGHAMBAT MIKROBA PERUSAK NIRA - Putro Utomo, Pramono (JURNAL BORNEO AKCAYA, 2016)
Jackfruit (Artocarpus heterophylla Lamk.) is a local plant where the tree is commonly used as a preservative for Cocos nucifera sap in a series of palm sugar manufacturing process. Chemical component in jackfruit wood that has potential as an antimicrobial, were morin, sianomaklurin, flavonoids, and tannins. The purpose of this study was to determine the antimicrobial activity of jackfruit wood extracts and antimicrobial activity of natural preservative formula with various concentrations of fillers. This study used extracts of jackfruit wood and excipients (maltodextrin) for formulating a natural food preservative. This research done by making sawdust jackfruit, extracting jackfruit wood with methanol and water, making the suspension with a concentration of fillers 15%, 20%, and 25% and make a natural preservative in the form of a powder using a spray drying method and analyze the antimicrobial activity in S. cerevisiae which is one cause of sap deterioration. The results showed that the jackfruit wood extract can inhibit the growth of yeast S. cerevisiae with a diameter of 6-15 mm zone of inhibition. Maltodextrin concentration which resulted in the most extensive inhibition zone diameter is 20% with a diameter of 9 mm zone of inhibition